Effects of water immersion ageing on the mechanical properties of flax and jute fibre biocomposites evaluated by nanoindentation and flexural testing. (May 2014) - Dhakal, HN; Zhang, ZY; Bennett, N; Lopez-Arraiza, A; Vallejo, FJ
Flax and jute fibres are inexpensive and easily available bast fibres and they are extensively used as reinforcement in polymer matrix composites. However, due to their susceptibility to moisture absorption, their application is restricted to non-structural interior products. In this study, flax- and jute fibre-reinforced bioresin-based epoxy biocomposites were fabricated using hand lay-up method and their nanoindentation and flexural properties were investigated. In order to study the effects of water absorption on the nanoindentation and flexural properties, the biocomposites were subjected to water immersion tests by immersing specimens in a de-ionised water bath at 25℃ for a period of 961 h. The nanoindentation behaviour and flexural properties of water-immersed specimens were evaluated and compared alongside with dry specimens. The percentage of moisture uptake and diffusion coefficient ( D ) was recorded higher for jute-reinforced specimens compared with flax. The flexural properties for both types of specimens were found to decrease with increase in percentage moisture uptake. Comparison of flexural strength and flexural modulus between flax dry and flax wet biocomposites showed that wet samples lost almost 40% of strength and 69% of modulus compared with dry flax samples. The jute wet samples lost 60% of strength and 80% of modulus compared with dry samples. The nanohardness value decreased from 0.207 to 0.135 GPa for dry flax sample after immersion in water.